A multi-regional structural path analysis of the energy supply chain in China's construction industry. (May 2016) - Hong, Jingke; Shen, Qiping; Xue, Fan
Abstract: The construction industry in China exerts significant environmental impacts and uses considerable resources because of rapid urbanization. This study conducted a structural path analysis (SPA) based on the multi-regional input–output table to quantify environmental impact transmission in the entire supply chain. Results indicated that the direct resource input (the first stage) along with on-site construction (the zeroth stage) consumed the highest amount of energy in the supply chain and accounted for approximately 50% of total energy consumption. Regional analysis showed that energy consumption in the construction industry at the provincial level was self-sufficient. Sectoral analysis demonstrated that the direct inputs from the sectors of "manufacture of non-metallic mineral products" and "smelting and pressing of metals" generated the most important energy flows, whereas the sectors of "production and distribution of electric power and heat power" and "extraction of petroleum and natural gas" significantly but indirectly influenced energy use. Sensitivity analysis exhibited that the system boundary of SPA could be narrowed down into the first two upstream stages that contained nearly 50% of energy flow information or expanded toward the first five upstream stages that represented 80% of total energy consumption. Highlights: We designed an optimized algorithm for multi-regional SPA. We extracted energy-intensive paths throughout the upstream supply chain. We explored self-sufficiency characteristic for provincial construction industries. We identified energy-intensive sectors hidden in higher-order supply chain. We developed an effective strategy for narrowing down the system boundary of SPA.